Pendidikan Multikultural: Membangun Harmonisasi dan Kerukunan Melalui Penguatan Nilai Toleransi Di Desa Mojorejo Kota Batu Jawa Timur - Taufikurrahman, Taufikurrahman; Fajrin, Megawati; Ali Efendi, M Sabilal; Riswan, Mokhamad (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
Religious tolerance is evidenced by the unification of society through togetherness. This indicates that the religious phenomenon that exists as a reality in the midst of society gets a positive response so it is interesting to study. Meanwhile, on the other hand, the discourse of strengthening the harmonization of plural society which is manifested in the attitude of religious tolerance, was born and proclaimed by various parties. Mojorejo Village, Batu City managed to get appreciation from the Batu City government in the form of giving an award as